2007
DOI: 10.1007/s11239-007-0078-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of mean platelet volume in triagging acute coronary syndromes

Abstract: In patients presenting with NSTE ACS, higher MPV, though there are overlaps among subgroups, indicates not only more risk of having NSTEMI but also ischemic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
63
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 26 publications
10
63
3
Order By: Relevance
“…[14][15][16] . The risk of restenosis following higher with patients has higher MPV [17][18][19][20][21][22][23] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] . The risk of restenosis following higher with patients has higher MPV [17][18][19][20][21][22][23] .…”
Section: Resultsmentioning
confidence: 99%
“…MPV and other platelet indices correlates not only an increased risk of non STEMI, but also ischemic complications 4 . Also some studies have reported an association between high MPV and poor prognosis in IHD, but few studies to determine relation between IHD and other platelet indices such PDW, P-LCR and PCT.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, MPV was evaluated in young patients with NSTE-ACS. Thrombogenic activity is known to be higher in NSTE-ACS, and it has been shown to play an essential role in the etiopathogenesis of NSTE-ACS (1,23). Likewise, MPV were found to be higher in myocardial infarction patients with normal coronary arteries (24).…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have reported elevated MPV which has been proposed as a cardiovascular risk factor and has been recognized as an independent risk factor for myocardial infarction and adverse cardiovascular events such as recurrent ischemia or death 27,28 . Several reports have also reported that MPV was associated with restenosis after primary coronary intervention 16,21 .…”
Section: Discussionmentioning
confidence: 99%